Development of a Smart Greenhouse Using Internet of Things Technology with Automated Environmental Control - เกตุษา ชุติมา; รัตนวงษ์ ศรันย์ภัทร; พรศิริ พิเชษฐ; ลอแท ชาคริตส์ (การประชุมวิชาการระดับชาติและนานาชาติ เบญจมิตรวิชาการ ครั้งที่ 16, 2026)
This research aims to develop a smart greenhouse capable of automatically controlling environmental conditions, focusing on temperature and soil moisture for optimal plant growth. The system employs an Arduino UNO R4 WiFi with soil moisture and DHT22 sensors. An experimental study was conducted using a prototype greenhouse by cultivating lettuce and comparing it with conventional cultivation over a period of 45 days. The system automatically controlled irrigation and ventilation based on predefined thresholds, with real-time monitoring via Arduino IoT Cloud. The results showed that the system maintained temperature and moisture within optimal ranges, resulting in consistent plant growth and improved quality compared to conventional methods. Additionally, water consumption and manual labor were reduced. The developed system demonstrates strong potential for smart agriculture applications and sustainable farming